The influence of β-Ga2O3 film thickness on the optoelectronic properties of β-Ga2O3@ZnO nanocomposite heterogeneous materials. (December 2021) - Xie, Yadong; Nie, Yuhan; Zheng, Ying; Luo, Yao; Zhang, Jianguo; Yi, Zao; Zheng, Fusheng; Liu, Li; Chen, Xifang; Cai, Pinggen; Wu, Pinghui
Abstract: Nanocomposite heterogeneous nanomaterials excellent optoelectronic properties have been widely used in the field of solar cells. In this research, β-Ga2 O3 @ZnO composite heterogeneous-material was successfully prepared by combining magnetron sputtering with hydrothermal method. The thickness of the surface β-Ga2 O3 was adjusted by controlling the magnetron sputtering time, and the influence of β-Ga2 O3 film thickness on the optoelectronic properties of β-Ga2 O3 @ZnO nanocomposite heterogeneous was systematically investigated. The morphology and microstructure of the samples were characterized by scanning electron microscope (SEM), X-ray diffractometer (XRD) and Raman spectroscopy. It is found that the proper thickness of β-Ga2 O3 can improve the surface morphology leading to the excellent light absorption performance. Furthermore, the band gap of β-Ga2 O3 @ZnO nanocomposite heterogeneous is smaller than that of pure ZnO and β-Ga2 O3 according to the visible light absorption test. This demonstrates that the β-Ga2 O3 coating cam expand the range of light absorption. Thus, the composite material showed excellent photoelectrochemical performance through the photocurrent test in the electrochemical workstation. The results indicate that β-Ga2 O3 @ZnO nanocomposite heterostructures have broad application potential in the field of optoelectronics. Graphical Abstract: We by magnetron sputtering and hydrothermal method with the method of preparation of a composite of Ga2 O3 @ZnO nano heterogeneous material, through characterization, found that the preparation of the Ga2 O3 @ZnO composite material, by controlling the Ga2 O3 film thickness, relative to the photocurrent of material preparation of pure ZnO nanorods are improved obviously, the absorption in the visible region of the there is a marked increase. ga1 Highlights: The combination of Ga2 O3 thin film and ZnO nanorod array can effectively improve the photoelectric conversion efficiency. The performance of the device has been improved due to its wider visible light absorption. The Ga2 O3 @ZnO material shows better photocurrent and impedance properties.